Naturalisasi bagi Pemegang Golden Visa untuk Memperoleh Kewarganegaraan Indonesia melalui Skema Citizenship by Investment: Studi Keimigrasian di Negara Eropa - Muhammad Nur Rohim (Jurnal Hukum Lex Generalis, 2025)
This research examines the complex intersection of Golden Visa policies, immigration mechanisms, and citizenship laws in between Portugal, Spain, and Indonesia. As investment migration programs gain popularity, they present unique challenges to existing legal frameworks designed to protect nation’s sovereignty and maintain stable domestic markets. The need of comparative legal analysis methodology, scrutinizing the legislative and regulatory approaches of the three countries, thus explores how Indonesia could balance the economic benefits of golden visa schemes with the imperative to prevent transnational crimes and mitigate adverse effects on local markets. The evolution and current state of golden visa policies in Europe, might affect the analysis of existing citizenship laws and their application to Citizenship by Investment in Indonesia.